A Little Solitaire : John Frankenheimer and American Film - Palmer, R. Barton, 1946-; Pomerance, Murray, 1946- (Book collections on Project MUSE., 2011)
Little Solitaire offers the only multidisciplinary critical account of Frankenheimer's oeuvre. Especially emphasized is his deep and passionate engagement with national politics and the irrepressible need of human beings to assert their rights and individuality in the face of organizations that would reduce them to silence and anonymity.